THE PLANTING CULTURE PRODUCTIVITY IN FIELD CONDITIONS OF POTATO PLANTS SANITATED IN VITRO, AT GROWTH REGULATOR VYMPEL IMPLEMENTATION - Семенчук, В. Г.; Недільська, У. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
Purpose: to determine the effect of growth regulator Vympel on plants for planting productivity from plants in vitro, in field conditions. The field trials have been set in selection-seed production rotation of the Bukovinian state agricultural research station. The previous one - winter wheat. Soil - heavy loam black soil, which contains 10 mg P205, 17 mg K20, and 15,4 mg N03 per 100 g of soil. The agrotechnique is commonly accepted for the zone. The trial has been conducted on plants for planting from plants in vitro in field conditions with two potato varieties: Skarbnytsya, Dovira. The grown plants are with well-developed root system, height 8-10 sm, with 4-6 leaves have been planted into the open soil, watering the planted ones. Before planting out into the open soil, the plants for planting root system water-soaking has been carried out in Vympel solution of different concentrations (according to the trial scheme), for 15-20 minutes. All the accountings and surveys have been carried out according to methodical recommendations about conducting experiments on potato. During the investigations of the effect of PGR Vympel on plants for planting productivity from plants Big poornH in vitro, it is established, that: at plants for planting root system water-soaking, before planting out into the open soil, in the preparation solution the plants for planting engraftment has increased on 5-7 %, comparing to the control, where the root system has been soaked just in water. Twofold Vympel treatment (soaking the plants for planting root system from plants in vitro in 2% Ta 3% solution of PGR Vympel + spraying with PGR Vympel in dosage 0,5 and 1kg/ha in budding phase) favored the mini-tubers yield increase on 1,1-4,0 t/ha on the variety skarbnytsya, and on 1,2-3,5 t/ha on the variety Dovira, compared to the control. At twofold treatment of plants for planting with Vympel (soaking of plants for planting root system from plants in vitro in 3% solution of PGR Vympel + spraying with PGR Vympel in dosage of 1 kg/ha in budding phase), the 28-60 mm tubers quantity has increased on the variety Skarbnytsya on 11%. The preparation implementation had no effect on plants viral infections. Optimization of approaches and methods concerning seed material usage, obtained in meristems culture in vitro at production of basic- and pre-basic potato planting material, with the aim of seed process intensification.